Exploring the determinants of happiness in Mexico: The interplay of social networks, psychological well-being, and socioeconomic factors (2024)
Over recent years, there has been significant growth in research on happiness. It is essential to understand the factors that affect people's well-being to develop effective government policies that aim to improve the quality of life for citizens in Mexico. Unfortunately, this subject has been under-explored, especially in the Mexican context, with limited studies focusing on the topic. This study aims to comprehensively review the current literature on happiness, social networking, psychological factors, and socioeconomic factors to identify the critical variables associated with the happiness of Mexican citizens. Further, based on data from Mexico's 2021 National Survey of Self-reported Well-being (ENBIARE), we conducted a rigorous examination of this dataset to identify the principal factors that impact the well-being of Mexican citizens, employing both exploratory and confirmatory factor analysis.